Effect of Pregnancy and Concomitant Antiretrovirals on the Pharmacokinetics of Tenofovir in Women With HIV Receiving Tenofovir Disoproxil Fumarate‐Based Antiretroviral Therapy Versus Women With HBV Receiving Tenofovir Disoproxil Fumarate Monotherapy. (22nd September 2020) - Bukkems, Vera E.; Smolders, Elise J.; Jourdain, Gonzague; Burger, David M.; Colbers, Angela P.; Cressey, Tim R.; ,
Abstract: Tenofovir disoproxil fumarate (TDF) is recommended as part of antiretroviral therapy (ART) for pregnant women with HIV and as monotherapy for pregnant women with hepatitis B virus (HBV) monoinfection at high risk of transmitting infection to their infants. Tenofovir (TFV) plasma exposures are reduced during pregnancy; however, concomitant antiretrovirals and the viral infection itself can also influence TFV pharmacokinetics. Our aim was to compare TFV pharmacokinetics in pregnant women receiving TDF‐based ART, with or without a ritonavir‐boosted protease inhibitor (r/PI), to pregnant women with HBV receiving TDF monotherapy. Non‐r/PI regimens were primarily integrase strand transfer inhibitors or nonnucleoside reverse transcriptase inhibitor–based regimens. Data were combined from a pharmacokinetic study of pregnant women with HIV on ART (PANNA), and a study assessing TFV pharmacokinetics in pregnant women with HBV (iTAP). A total of 196 pregnant women, 59 with HIV (32 receiving r/PIs) and 137 with HBV monoinfection were included. Intraindividual TFV area under the plasma concentration–time curve from time 0 to 24 hours was 25%, 26%, and 21% lower during the third trimester compared to 1 month postpartum in women with HIV using TDF and an r/PI or TDF and non‐r/PI and women with HBV receiving TDF monotherapy, respectively. TFV area under the plasma concentration–time curve from time 0 to 24 hours was similar in pregnant women receiving non‐r/PI to pregnant women with HBV receiving TDF monotherapy (1.84 vs 1.86 µg h/mL); however, pregnant women receiving TDF with an r/PI had higher exposures (2.41 µg h/mL; P < .01). Pregnancy reduces TFV exposure and the relative size was not impacted by concomitant antiretroviral drugs or viral infection, but a drug‐drug interaction between TDF and r/PI remains during pregnancy, leading to higher exposures than those on TDF and non‐r/PI or TDF monotherapy.